Efeito do armazenamento em água sobre a citotoxicidade de materiais resilientes para base de próteses. - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2010)
The aim of this study was to evaluate the effect of water storage time and of a heat treatment on the cytotoxicity of soft lining denture material using the 3H-thymidine incorporation test. Sample disks (10 mm X 1 mm) of soft lining denture Dentusoft, Dentuflex, Trusoft, Ufi Gel P and of denture base acrylic resin Lucitone 550 were fabricated under aseptic conditions. Twelve specimens of each material were prepared and divided into four groups: GN: The specimens received no treatment or storage in water, G24: The specimens were stored in distilled water at 37°C for 24 hours; G48: The specimens were stored in distilled water at 37°C for 48 hours, GHW: The specimens were immersed in water at 55 °C for 10 minutes. To analyze the cytotoxic effect, three samples of each experimental group were placed in test tubes with 9 ml of DMEM's medium supplemented and incubated at 37 °C for 24 hours. During this incubation period, the toxic substances were broadcast to the culture medium, forming the extracts that were used for the cytotoxicity test. The cytotoxicity of each material was analyzed quantitatively by the incorporation of radioactivity 3H - thymidine by checking the number of viable cells for the synthesis of DNA. The results of DNA synthesis were subjected to analysis of variance in a factorial two-way (material and storage time in water). Comparing the averages of cell viability with the classification of cytotoxic established by ISO 10993-5, it was found that Ufi Gel P had non-cytotoxic effect, Trusoft had slightly cytotoxic effect, Dentuflex had a moderated cytotoxic effect, all in any experimental condition. It was also observed that the Dentusoft alternated between slightly cytotoxic and non-cytotoxic effect because their average viability ranged around 75% and Lucitone 550 had non-cytotoxic effect when stored in water for 48 hours, but the others had around 50% cell viability, the slightly moderated cytotoxic effect. It is concluded that the soft lining denture based in acrylic resin had a slightly and moderated cytotoxic effect, Ufi Gel P, the silicone based soft liner, was not cytotoxic; the effect of water storage after 24 hours or 48 hours and the heat treatment did not reduce the cytotoxicity effect of soft lining denture materials.
Efect of water storage on the cytotoxicity of resilient liners
Keywords: reembasadores de dentadura; citotoxicidade inmunológica; timidina.; soft liners; cytotoxicity; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA